Self-assembly of hydrogen-bonded comb copolymer complexes of poly(p-hydroxystyrene) and 4-alkylpyridine amphiphiles. (1st June 2016) - Faber, Martin; Hofman, Anton H.; Harinck, Nanda; ten Cate, Mark; Loos, Katja; ten Brinke, Gerrit
Abstract: The self-assembly of the hydrogen-bonded complexes between poly( p -hydroxystyrene) (P p HS) and 4-alkylpyridine amphiphiles is studied using infrared spectroscopy, differential scanning calorimetry, polarized optical microscopy, transmission electron microscopy and small- and wide-angle X-ray scattering. Interesting differences are observed with the well-studied inverted system of poly(4-vinylpyridine) and alkylphenol amphiphiles. When the alkyl tails of the 4-alkylpyridine amphiphiles are long enough, 19 and 21 respectively, an ordered lamellar structure is formed on cooling where the ordering and crystallization of the alkyl tails occur quasi simultaneously. For a shorter alkyl tail of length 17 no ordered structure is formed. This is quite different from the inverted P4VP/alkylphenol systems, where already for an alkyl tail of length 15, i.e., pentadecylphenol, an ordered structure is formed below ca. 55 °C, followed by crystallization of the alkyl tails at ca. 20 °C. This can be attributed to the possibility of (intramolecular) hydrogen bond formation of P p HS. Graphical abstract: Highlights: Poly( p -hydroxystyrene) was synthesized via anionic polymerization. Self-assembly of hydrogen-bonded comb copolymer complexes poly( p -hydroxystyrene) with various 4-alkylpyridines was studied. Ordered structures are observed in which the disorder-order transition and crystallization occur quasi simultaneously. No liquid crystalline ordering can be observed.